Sing out! [Bladmuziek] (Hamburg: Sing Out Corporation, 1985)
"Deze brochure bevat volgende liederen :Auld Lang SyneFine Flowers in The ValleyWhat's HappeningBirthday CakeDust My BroomDrop Down MamaBarstowTestimonyThe ReturnArtifical MeansNo Más!Steppin' OutAppleseedsPrecious Friend (You will be there)You Say The Ballte Is OverOne Kind FavorBanty RoosterJust An Old WomenThe Gooey-Duck SongAscending WomanGypsyThe Color SongYour Daughters And Your Sons"